Incomplete cellular reprogramming of colorectal cancer cells elicits an epithelial/mesenchymal hybrid phenotype - Hiew, Michele Sook Yuin; Cheng, Han Ping; Huang, Chiu Jung; Chong, Kowit Yu; Cheong, Soon Keng; Choo, Kong Bung; Kamarul, Tunku (BMC, 2018)
Background: Induced pluripotency in cancer cells by ectopic expression of pluripotency-regulating factors may be used for disease modeling of cancers. MicroRNAs (miRNAs) are negative regulators of gene expression that play important role in reprogramming somatic cells. However, studies on the miRNA expression profile and the expression patterns of the mesenchymal-epithelial transition (MET)/epithelial-mesenchymal transition (EMT) genes in induced pluripotent cancer (iPC) cells are lacking. Methods: iPC clones were generated from two colorectal cancer (CRC) cell lines by retroviral transduction of the Yamanaka factors. The iPC clones obtained were characterized by morphology, expression of pluripotency markers and the ability to undergo in vitro tri-lineage differentiation. Genome-wide miRNA profiles of the iPC cells were obtained by microarray analysis and bioinformatics interrogation. Gene expression was done by real-time RT-PCR and immuno-staining; MET/EMT protein levels were determined by western blot analysis. Results: The CRC-iPC cells showed embryonic stem cell-like features and tri-lineage differentiation abilities. The spontaneously-differentiated post-iPC cells obtained were highly similar to the parental CRC cells. However, down-regulated pluripotency gene expression and failure to form teratoma indicated that the CRC-iPC cells had only attained partial pluripotency. The CRC-iPC cells shared similarities in the genome-wide miRNA expression profiles of both cancer and pluripotent embryonic stem cells. One hundred and two differentially-expressed miRNAs were identified in the CRC-iPC cells, which were predicted by bioinformatics analysis be closely involved in regulating cellular pluripotency and the expression of the MET/EMT genes, possibly via the phosphatidylinositol-3 kinases-protein kinase B (PI3K-Akt) and transforming growth factor beta (TGF-β) signaling pathways. Irregular and inconsistent expression patterns of the EMT vimentin and Snai1 and MET E-cadherin and occludin proteins were observed in the four CRC-iPC clones analyzed, which suggested an epithelial/mesenchymal hybrid phenotype in the partially reprogrammed CRC cells. MET/EMT gene expression was also generally reversed on re-differentiation, also suggesting epigenetic regulation. Conclusions: Our data support the elite model for cancer cell-reprogramming in which only a selected subset of cancer may be fully reprogrammed; partial cancer cell reprogramming may also elicit an epithelial-mesenchymal mixed phenotype, and highlight opportunities and challenges in cancer cell-reprogramming.